LRG1 promotes metastatic dissemination of melanoma through regulating EGFR/STAT3 signalling - Kwan, Yuet Ping; Teo, Melissa Hui Yen; Lim, Jonathan Chee Woei; Tan, Michelle Siying; Rosellinny, Graciella; Wahli, Walter; Wang, Xiaomeng (Multidisciplinary Digital Publishing Institute, 2021)
Although less common, melanoma is the deadliest form of skin cancer largely due to its highly metastatic nature. Currently, there are limited treatment options for metastatic melanoma and many of them could cause serious side effects. A better understanding of the molecular mechanisms underlying the complex disease pathophysiology of metastatic melanoma may lead to the identification of novel therapeutic targets and facilitate the development of targeted therapeutics. In this study, we investigated the role of leucine-rich α-2-glycoprotein 1 (LRG1) in melanoma development and progression. We first established the association between LRG1 and melanoma in both human patient biopsies and mouse melanoma cell lines and revealed a significant induction of LRG1 expression in metastatic melanoma cells. We then showed no change in tumour cell growth, proliferation, and angiogenesis in the absence of the host Lrg1. On the other hand, there was reduced melanoma cell metastasis to the lungs in Lrg1-deficient mice. This observation was supported by the promoting effect of LRG1 in melanoma cell migration, invasion, and adhesion. Mechanistically, LRG1 mediates melanoma cell invasiveness in an EGFR/STAT3-dependent manner. Taken together, our studies provided compelling evidence that LRG1 is required for melanoma metastasis but not growth. Targeting LRG1 may offer an alternative strategy to control malignant melanoma.